Measuring the self-efficacy of virtual leaders - Couture, Kelsey Len (Kansas State University, 2020)
Accurately measuring the phenomena we intend to study is a foundational aspect of research and practice. Thus, the focus of this research was to develop a measure of Virtual Leader Self-Efficacy (VLSE), which had not been examined in the past. Two studies were conducted. The first served to develop the scale based on well-tested guidelines. A unidimensional factor structure was identified, and high reliability was maintained with very few items. A parallel form and an additional VLSE Trust scale was developed as well. The second study served to validate the scales and confirm the previous factor structure. By developing a reliable and valid measure of virtual leader self-efficacy, this study provides a robust foundation for future research in this area. Practical implications, strengths, limitations, and future directions of the research are discussed.
Keywords: self-efficacy; teams; communication; trust; shared leadershipVirtual leadership